2020
DOI: 10.1097/scs.0000000000006108
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Primary Acquired Nasolacrimal Duct Obstruction, Paranasal Abnormalities and Nasal Septal Deviation

Abstract: Objectives: This study aimed to investigate the relationship between nasal septal deviation and paranasal abnormalities in the etiology of primary acquired nasolacrimal duct obstruction (PANDO). Methods: A total of 37 (8 men, 29 women) patients (48 eyes with PANDO) between the ages 20 and 77 years (mean age, 52.8 ± 13.1 years) were included in the study. In the axial sections of paranasal sinus computed tomography, the transverse diameters at the most u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…While it is still uncertain how the narrower inferior turbinate angle is related to the obstruction, this may be because the narrower inferior turbinate angle affects the opening site of the lacrimal drainage system. In contrast to some previous results (15,(17)(18)(19)(20), nasal septal deviation, concha bullosa, and inferior turbinate thickness were found to be not associated with PANDO. The prevalence of sinus inflammation shown by CT in the healthy controls was similar to the result of a previous study (23).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…While it is still uncertain how the narrower inferior turbinate angle is related to the obstruction, this may be because the narrower inferior turbinate angle affects the opening site of the lacrimal drainage system. In contrast to some previous results (15,(17)(18)(19)(20), nasal septal deviation, concha bullosa, and inferior turbinate thickness were found to be not associated with PANDO. The prevalence of sinus inflammation shown by CT in the healthy controls was similar to the result of a previous study (23).…”
Section: Discussioncontrasting
confidence: 99%
“…This study applied widely used methods to measure the nasal quantitative structure. Two nasal structure parameters were measured on the coronary section according to previously reported methods ( 20 , 21 ), including inferior turbinate thickness and inferior turbinate angle (the angle between the bony inferior turbinate and the medial wall of the maxillary sinus), which reflected the relative position of the inferior turbinate ( Figure 1F ). Nasal abnormalities included nasal septal deviation, concha bullosa, and the inflammation of the frontal sinus, maxillary sinus, ethmoid sinus, osteomeatal complex (the common channel linking the frontal sinus, anterior ethmoid air cells, and the maxillary sinus to the middle meatus), and agger nasi cells (the most anterior ethmoidal air cells lying inferior to the frontal recess).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, in the present study, we analyzed the distribution of the volume of the inferior nasal conchae in patients of different groups, since the literature contains information that hypertrophy of the inferior nasal conchae may be one of the factors contributing to the development of nasolacrimal duct obstruction. 11 12 13 Fig. 3b shows the process of measuring the volume of the inferior nasal concha.…”
Section: Discussionmentioning
confidence: 99%
“…5 The bony structures of the nasolacrimal duct are located in the lateral nasal wall, suggesting that the structural abnormalities of this duct system may be affected by pathologies of the nasal cavity. 6 In a previous study on adult patients, a statistically signi cant relationship was found between acquired nasolacrimal duct obstruction (acquired NLDO) and NSD. 7 There are other studies that examined nasal pathologies and nasolacrimal duct obstruction in adult patients.…”
Section: Introductionmentioning
confidence: 90%